Conference – 2015 Equation

Y i t = β X i t + α S i Z i t + ε i t MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaamywamaaBa aaleaacaWGPbGaamiDaaqabaGccqGH9aqpcqaHYoGycaWGybWaaSba aSqaaiaadshacaWGPbaabeaakiabgUcaRiabeg7aHjaadofadaWgaa WcbaGaamyAaaqabaGccaWGAbWaaSbaaSqaaiaadMgacaWG0baabeaa kiabgUcaRiabew7aLnaaBaaaleaacaWGPbGaamiDaaqabaaaaa@4AA7@